PENGARUH PRODUK DAN PROMOSI TERHADAP KEPUTUSAN NASABAH MENABUNG DI BANK SYARIAH INDONESIA KC JAMBI PATTIMURA DENGAN RELIGIUSITAS SEBAGAI VARIABEL MODERATING - Selbi, Selbi; Addirahman, Addirahman; Siregar, Fitri Ana (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is motivated by the instability of customers who are still experiencing ups and downs of customers. The purpose of this study was to determine the effect of products and promotions on customers' decisions to save in Islamic banks with religiosity as a moderating variable. This study used a quantitative method with a sample of 100 respondents and a non-probability sampling technique. The data analysis tool in this study used moderated regression analysis (MRA), which was processed using the IBM SPSS Statistics 25 tool. The results of this study have an influence on the customer's decision to save at Bank Syariah Indonesia KC Jambi Pattimura with a significance value of 0.001 <0.05. Promotion has an influence on customers' decisions to save at Bank Syariah Indonesia KC Jambi Pattimura with a significance value of 0.000 < 0.05. Simultaneously, the product and promotion variables influence the customer's decision to save at Bank Syariah Indonesia KC Jambi Pattimura with a significance value of 0.000 < 0.05. And the Religiosity variable is known that the significant value of 0.000 is less than 0.05 and the R Square value is 0.821 meaning that religiosity moderates the simultaneous effect of product and promotion on customers' saving decisions